AB0904 Fusobacterium necrophorum masquerading as neisseria in septic arthritis. (15th June 2017) - O'neill, CH; McCormick, H; Leith, M; McCorry, L; McKenna, J; Pendleton, A; Protaschik, Y; Loughrey, A; Coyle, PV; Fairley, D
Abstract : Background: Infective arthritis with fusobacterium is rare and difficult to diagnose & initially can be misidentified as Neisseria arthritis based on microscopy results. It is associated with Lemierre's Disease & is important to recognise. Objectives: To demonstrate that a "linked up" approach between culture and PCR in the analysis of joint fluids will provide timely identification of the organism and allow for appropriate antibiotic use & to show the utility of bacterial 16S rRNA PCR in sterile site fluid analysis. Methods: This is a case study of a pyogenic wrist infection with Fusobacterium necrophorum in the rheumatology department Results: Our report follows a 17 year old caucasian female presenting with a history of left wrist pain, swelling and flu-like symptoms. Microscopy of joint aspirate revealed gram negative diplococci. Empirical antibiotic therapy, Ceftriaxone, was used to cover for potential gonococcus. Real-time PCR testing was negative for both gonococcus and meningococcus. However a real-time PCR assay targeting the bacterial 16S ribosomal RNA gene detected bacterial DNA 1 . The patient did not clinically improve and further aspirate remained positive for the 16S rRNA gene target. As all joint aspirates and other specimens remained culture negative, the decision was taken to attempt bacterial 16S rRNA PCR and sequencing on DNA extracted directly from the joint aspirate. The sequences recovered were identified as F necrophorum . This was eventually confirmed by anaerobic culture of the initial joint aspirate. A suspicion of Lemierre's disease (thrombophlebitis of the internal jugular vein and/or bacteraemia) was raised, however jugular venous dopplers were normal. The outcome was favourable following guided antibiotic treatment. Conclusions: This case illustrates that F. necrophorum infection may occur with unusual or disseminated presentation, but in the absence of the classical features of Lemierre's syndrome. The possibility of Neisseria was recognised early & appropriate empirical antibiotic cover was used. This is important given the emergence of virulent meningococcal serogroup W ST11 strains causing infections with unusual presentation (including septic arthritis) in the UK 2 . Reliance on microscopy findings alone could have led to an incorrect diagnosis of gonococcal septic arthritis – a condition with very low complication rates and excellent prognosis. In contrast, non-gonococcal septic arthritis is a medical emergency with significant morbidity and mortality 3 . The F. necrophorum infection in this case could have had fatal complications if it had been managed as a gonococcal infection. Secondly this case highlights the utility of bacterial 16S PCR and sequencing directly from a normally sterile site, allowing accurate diagnosis and appropriate treatment. References: Yang S et al (2002)Quantitative Multiprobe PCR Assay for Simultaneous Detection and Identification to Species Level of Bacterial Pathogens J Clin Micro 40(9):3449–3454. Ladhani SN, et al(2014) Increase in Endemic Neisseria meningitidis Capsular Group W Sequence Type 11 Complex Associated With Severe Invasive Disease in England and Wales. Clinical Infectious Disease 60:578–585. Shirtliff & Mader (2002) Acute septic arthritis. Clin Microbiol Rev. 15(4):527–44. Disclosure of Interest: None declared